Legislative norms and prohibitions on anonymous commenting on the internet: realities of Kazakhstani media (Herald of Journalism, 2023)
The article considers the problems of implementation process of internet-commenting as one type of interactive behavior of Kazakhstani web audience under the influence of the legislative norms and trends of the global media market. In particular, proves that there is a correlated dependence between website traffic and restricting on commenting. Use of common theoretical and empirical research methods: analysis, synthesis, deduction, induction, extrapolation, observation, comparison, historical method - allowed to reflect modern possibilities of carrying out an interactive connection of websites with users in the light of limitations related to news commenting. The analysis of the real empirical material (Kazakhstani websites) has also contributed to achieving the goal of the study. The scientific importance of work lies in the analysis and providing possible solutions of the mentioned problems. In this connection, the influence of global media market trends on the formation of media behavior in the Kazakhstan segment of the Internet is methodologically studied. The main results of the work are the results of the analysis of the current situation around internet commenting on the websites of Kazakhstani media and social networks. The analysis of Kazakhstani websites such as: nur.kz, azattyk.org, informburo.kz, tengrinews.kz, time.kz, caravan.kz and regional websites such as: Kostanayskie Novosti and Nasha Gazeta, leads to the conclusion that the current situation with the prohibition of the anonymous commenting on the Kazakhstani websites and the shift of this feature to social media platforms are not normal. There are real examples of foreign media using the opportunity to comment on the site as a privilege for paid subscribers also presented in the study. Also approved that such a way of converting registered users into paid subscribers can become fruitful both in the context of the manifestation of social activity of the publication's audience, and cost-effective in the practice of the existence of modern Kazakhstani media on the information market.Keywords: commenting on news, media behavior, web audience, social networks, legislative norms.